The effect of executive compensation and institutional ownership on tax aggressive actions with firm size as an intervening variable - Diah Intan Syahfitri; Reza Muhammad Rizqi; Arya Zulfikar Akbar (Institute of Computer Science (IOCS), 2023)
This study intends to investigate how the effect of Executive Compensation and institutional ownership on the level of aggressiveness in the application of tax regulations. Purposive sampling was used to select a sample of 140 manufacturing companies which are traded on the Indonesia Stock Exchange. In this study, we used SEM-PLS, Executive compensation (X1) was found to have a large effect on tax aggression (Y) while controlling for business size (Z). Firm size (Z) has a positive effect on the relationship between executive compensation (X1) and tax aggressiveness (Y). Firm size (Z) and institutional ownership (X2) both have a significant effect on tax aggressiveness (Y). Business size (Z) has a positive effect on the relationship between institutional ownership (X2) and tax aggression (Y). Interesting understanding of aggressive tax practices can have significant consequences both for companies and for society at large. By understanding the factors that influence this practice, this research can provide better insight into the causes and effects of aggressive taxation measures. This research is expected to contribute to the development of knowledge about the factors that influence tax aggressiveness in companies, so that it can assist in the development of better policies and practices in the context of corporate taxation.